2021
DOI: 10.3389/fpain.2021.713430
|View full text |Cite
|
Sign up to set email alerts
|

Initial Adjustment to the COVID-19 Pandemic and the Associated Shutdown in Children and Adolescents With Chronic Pain and Their Families

Abstract: Objectives: Youth with chronic pain often struggle to function in multiple domains due to pain and associated psychosocial distress. In 2020, schools and businesses shut down and people were encouraged to remain at home due to the COVID-19 pandemic, eliminating or reducing stress due to functional difficulties. This study assessed whether pain and associated psychosocial outcomes improved in youth with chronic pain during the shutdown, compared with before the pandemic.Methods: Patients who completed clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…For example, the deleterious impact of the COVID-19 pandemic on parent mental health 26 may have understandably made it more difficult for some parents to participate. Further, the challenges related to screen/virtual fatigue has impacted enrolment in other forms of pediatric chronic pain research during the pandemic, 27 demonstrating that easier intervention access may not necessarily increase enrolment. Based on a content analysis of open-ended written feedback from parents posttreatment, there appears to be strong support for the group-based nature of the intervention, given that the social support and the validation/normalization that parents experienced were noted as their most liked components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the deleterious impact of the COVID-19 pandemic on parent mental health 26 may have understandably made it more difficult for some parents to participate. Further, the challenges related to screen/virtual fatigue has impacted enrolment in other forms of pediatric chronic pain research during the pandemic, 27 demonstrating that easier intervention access may not necessarily increase enrolment. Based on a content analysis of open-ended written feedback from parents posttreatment, there appears to be strong support for the group-based nature of the intervention, given that the social support and the validation/normalization that parents experienced were noted as their most liked components.…”
Section: Discussionmentioning
confidence: 99%
“…However, preliminary results demonstrated a nonsignificant change in school attendance for inperson groups and a significant improvement in school functioning for the virtual groups from baseline to posttreatment, which was maintained at follow-up. Research on the impact of COVID-19 on school functioning in youth with chronic pain is very limited; 1 study reported that many youths with chronic pain endorsed difficulties with school functioning during the initial shutdowns of the pandemic, 27 although longitudinal or comparative data were not reported. Thus, it is not yet clear how/whether the Covid-19 pandemic impacted school functioning in youth with chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Among youth with prepandemic chronic pain, researchers predominantly found stable or improved pain symptoms during the first few months of the pandemic. 15,21,24,38,47,50 In addition, a longitudinal study conducted in a German school–based sample (n = 777, age 9-17 years) found a prevalence of chronic pain 22% lower in October or November 2019 relative to June or July 2020. 42 Studies among adults with chronic pain, including clinical and online survey samples, also reported predominant stability or improvement in pain outcomes during the early pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,43 Studies with youth who had received care for chronic pain before the pandemic suggest an overall stability or improvement in pain-related symptoms during the early stages of the pandemic. 21,24,33,38,47,50 A study from Germany also found an overall decrease in chronic pain prevalence in a school-based sample from October or November 2019 to June or July 2020. 42 However, these studies are limited to clinical or regional samples which may differ from the US general population in underlying risk and protective factors for pediatric chronic pain, as well as in the pandemic experience.…”
Section: Introductionmentioning
confidence: 95%
“… 20 Despite the onset of both new symptoms as well as exacerbations of preexisting pain, many youth and families experienced reduced access to both medical and mental health care during the pandemic. 23 , 24 These circumstances contributed to patients reporting increased anxiety, fear, and helplessness and, in some cases, resulted in delayed diagnoses and higher complication rates. 25 Prior to the COVID-19 pandemic, the role of family had been shown to be especially influential on pediatric pain experiences as well as quality of life.…”
Section: Introductionmentioning
confidence: 99%